Arabian Partridge Abundance and Limiting Factors at the Northern Boundary of Its Range - Soultan, Alaaeldin; Shah, Moayyed Sher; Almalki, Ahmed Mohammed; Browne, Stephen; Arcilla, Nico (Birds (Basel, Switzerland), 2023)
The Arabian Partridge (Alectoris melanocephala), is an endemic bird species of the Arabian Desert that lives in groups and inhabits rocky hillsides with patchy vegetation. Throughout their range, Arabian Partridges contend with hunting and habitat destruction, factors that may limit their distribution and abundance. Although the abundance of this species has been assumed to be stable, no actual estimate of its population size has been undertaken. We assessed the distribution and estimated the abundance of the Arabian Partridge at the northern boundary of its range in Saudi Arabia. The estimated density and abundance of the Arabian Partridge in Harrat Uwayrid Biosphere Reserve was 25.6 (6.16 SE) birds/km2 and ~118 individuals, respectively, with higher numbers of individuals in less disturbed sites and near rocky outcrops and hillsides. In sites where hunting occurred, as indicated by the presence of hunting shelters, partridge numbers were extremely low or absent. Our study provides the first quantitative assessment of the Arabian Partridge at the northern limit of its range and highlights the need to reduce threats from hunting, livestock grazing, and feral donkeys and to undertake conservation measures to mitigate factors associated with partridge decline.